Tam Approach: The Role Of Perceived Usefulness On Attitude In The Use Of Hospital Applications In Indonesia - Rizkaully Permatasari Fitrianingsih; Hasyim Hasyim; Rokiah Kusumapradja (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The development of information technology has changed the way patients interact with hospitals. The Minimum Service Standard Indicator for Hospitals in Indonesia shows that the number of registrations via mobile applications has still not reached the target and the results of the review show that there are still complexities and difficulties in using the application. Understanding the factors that influence patient intention to use the hospital mobile application is essential to optimize its adoption and use. This study aims to test the Technology Acceptance Model in understanding patient intention to use the Hospital mobile application. This quantitative study with the causality method used a sample of 100 users of the application who met the criteria. Data were collected through questionnaires and analyzed using path analysis. The results showed that perceived ease of use and perceived usefulness had an indirect effect on behavioral intention to use through attitude. Research findings show that Perceived Usefulness is the most dominant factor in influencing users attitudes towards applications. The implications are improvements in simplifying features, design, increasing the function of hospital mobile applications, as well as considering patient expectations of the application in order to increase user intention to adopt the application. These findings provide insight for hospital management to design mobile applications that are easier to use and provide benefits to patients, to increase adoption and use of the application.